The euro sovereign debt crisis, determinants of default probabilities and implied ratings in the CDS market: an econometric analysis - Santos, Carlos (2014)
In this paper, we investigate what has been leading investors to ask for higher yields on sovereign debt from certain Euro countries. We dismiss Granger Causality as a basis to define speculation. Instead, we assume that speculative behavior would only exist if market assessments were unrelated to economic fundamentals. Using a cross section of countries, we improve on the literature on Credit Default Swap Markets on sovereign debt. Firstly, we use an ordered probit to determine whether fundamentals are driving ratings. Then, quantile regression determines which variables matter at different conditional quantiles of the default probability. Finally, Fisher’s Z statistic is used to relate bond yields to domestic savings. The different methods support the conclusion that the domestic savings rate is lenders’ main concern. Economies with worse saving habits are penalized both in the CDS and in the bonds market. Notwithstanding, for countries on the top quantiles of the default probabilities, public and external debt also increase the insurance premium in the derivatives market. Looking at the Portuguese case, it is clear that policies that don’t take savings into account shall fail, as the country had the lowest net savings rate in the EU27 in 2008, followed closely by Greece